Penerapan Green Accounting Dalam Pengelolaan Tempat Wisata Hutan Mangrove Di Surabaya - Sunia Apriyono; Naafika Rachma Rozani; Dyah Putri Agustin; Maria Yovita R Pandin (Pusat Riset dan Inovasi Nasional, 2023)
Green accounting is an accounting approach that focuses on measuring, reporting and controlling economic activity that takes into account environmental impacts. The research objective of Mangrove Forest Tourism in Surabaya is to determine tourism potential and attractiveness, development strategy and community and government participation in the development of objects and attractions for Mangrove Forest Tourism in Surabaya. This tour provides beautiful scenery as well as exciting and educational. The results of this study are the implementation of Mangrove Forest management as a tourist spot in Surabaya which is quite good and has proven to be able to attract visitors and improve the economy of the local community in the area.